2001
DOI: 10.1054/bjoc.2001.1964
|View full text |Cite
|
Sign up to set email alerts
|

Kirsten ras mutations in patients with colorectal cancer: the ‘RASCAL II’ study

Abstract: SummaryResearchers worldwide with information about the Kirsten ras (Ki-ras) tumour genotype and outcome of patients with colorectal cancer were invited to provide that data in a schematized format for inclusion in a collaborative database called RASCAL (The Kirsten ras incolorectal-cancer collaborative group). Our results from 2721 such patients have been presented previously and for the first time in any common cancer, showed conclusively that different gene mutations have different impacts on outcome, even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

46
538
8
23

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 783 publications
(622 citation statements)
references
References 3 publications
46
538
8
23
Order By: Relevance
“…Oncogenic activation of RAS signaling pathways has been implicated in many aspects of the malignant process, including abnormal cell growth, proliferation, and differentiation. KRAS mutations are, in most cases, an early event in the development and progression of colorectal cancers [56,58,59]. Consistent with this concept, several studies have demonstrated that KRAS mutation status is an important prognostic factor in colorectal cancer [55,[58][59][60].…”
Section: Kras: a Downstream Target Of Egfr Signalingmentioning
confidence: 83%
See 2 more Smart Citations
“…Oncogenic activation of RAS signaling pathways has been implicated in many aspects of the malignant process, including abnormal cell growth, proliferation, and differentiation. KRAS mutations are, in most cases, an early event in the development and progression of colorectal cancers [56,58,59]. Consistent with this concept, several studies have demonstrated that KRAS mutation status is an important prognostic factor in colorectal cancer [55,[58][59][60].…”
Section: Kras: a Downstream Target Of Egfr Signalingmentioning
confidence: 83%
“…Consistent with this concept, several studies have demonstrated that KRAS mutation status is an important prognostic factor in colorectal cancer [55,[58][59][60]. KRAS mutations are associated with tumors of more advanced stage, increased metastatic potential, poor prognosis, and decreased PFS and OS of patients [55,56,58,59]. The prognostic value of KRAS mutations in colorectal cancer is presently controversial and warrants further confirmation.…”
Section: Kras: a Downstream Target Of Egfr Signalingmentioning
confidence: 94%
See 1 more Smart Citation
“…Our exon 2 KRAS mutation rate of 28% is in agreement with previous studies when mutations in exon 2 only are considered. 10,11,16,17 Like BRAF-mutated carcinomas, KRAS-mutated carcinomas showed an increased frequency of mucinous differentiation. This finding has been previously observed by Lin et al 28 and more recently by Pai et al, 8 who reported that 32% of proximal KRAS-mutated carcinoma showed mucinous differentiation compared with 25% of null carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…7,10,11 The overwhelming majority of KRAS mutations (90%) occur in codons 12 and 13 of exon 2, with the most frequent alteration being a G4A transition in codon 12. 12 The clinical significance of KRAS mutation in colorectal carcinoma patients is controversial; some studies reported no association with survival, 13,14 whereas others suggested that patients with KRASmutated colorectal carcinoma have poorer outcome for any mutation subtype, 15 mutation in codon 12 only 16,17 or codon 13 only. 11 There is more definitive evidence for a negative predictive value of KRAS mutation in patients with advanced stage disease treated with targeted anti-EGFR monoclonal antibody drugs.…”
mentioning
confidence: 99%